(untitled) (Comparative & International Education Series, 2022)
Focusing on critical employability for students is important because colonialism, in its various forms, influences student development of self and affects how a student develops and uses their agency to understand employability pathways. This chapter unpacks various definitions and theories to explain the dimensions of employability within the socio-economic and political environment. We argue that capturing student voices and sensemaking of their international experience will broaden their understanding of how studying abroad relates to critical employability development.